Analysis of The Requirements for Teaching Materials on Maritime Contents in Bipa Learning on the Riau Island - Fabio Testy Ariance Loren; Dody Irawan (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
Learning Indonesian for Foreign Speakers (BIPA), which is increasingly in demand, must of course maintain the achievement of learning objectives. However, in reality, the material learned in class is different from the conditions of the environment. Therefore, this study aims to analyze maritime-based teaching materials in Indonesian language learning for foreign speakers. This study uses a qualitative approach with interview data collection techniques, questionnaire, and document analysis. The research subjects are BIPA documents, BIPA teachers and students in the Riau Islands. Based on the results of the analysis of Indonesian language skills, BIPA students in the Riau Archipelago find it very difficult to master special vocabulary related to maritime which is 45.5%. While the results of document analysis on competency standards for BIPA graduates and the Sahabatku Indonesia textbook published by the Language and Book Development Agency show that the material presented in BIPA learning is only general in nature. As for the maritime-charged material from level 1 to level 7, only 2,2%. Meanwhile, teachers and students said that they only gave direct practice to the field of maritime affairs. The needs of BIPA students for maritime teaching materials also reach a very large percentage of the data resulting from the questionnaire, which is 100%.Keywords: Teaching Materials, Maritime, BIPA